Comparison of Trauma in Dogs due to Direct Motor Vehicle Collision or Fall from Open Pick-up Truck Bed during Transportation (2002-2020) - Salmelin, Bettina R.M.; Ueda, Yu; Gilbert, Peter J.; Martinez, Steven A. (Veterinary and Comparative Orthopaedics and Traumatology, 2022)
Objective The aim of this study was to report injuries sustained by dogs following motor vehicle trauma: direct motor vehicle collision (MVC), and fall from an open pickup truck bed during transportation (PTB).Study Design Medical records of dogs involved in motor vehicle trauma between 2002 and 2020 were reviewed. Signalment, mode of injury, injuries sustained, and treatments performed were recorded. An owner questionnaire investigated effects of the trauma on the dog and owner.Results Six hundred and ninety-eight dogs met the inclusion criteria (569 MVC, 102 PTB). Orthopaedic trauma was significantly more common after PTB (90.2%) (MVC, 75.6%; p = 0.011). There were not any differences in the prevalence of soft tissue injuries between groups (76.4% MVC, 67.6% PTB; p = 0.058), however, MVC dogs had significantly more thoracic (26.9% MVC, 4.4% PTB) and abdominal (12.9% MVC, 0% PTB) trauma (p <0.001). Surgical treatments were performed significantly more often after PTB (71.6%) (MVC, 47.6%) (p <0.001). Discharge rate after PTB (95.0%) was significantly higher (MVC, 84.0%) (p <0.001). Aftercare was reported to be significantly more difficult after PTB (76.2%) (MVC, 34.0%; p = 0.002).Conclusion MVC and PTB result in significantly different trauma. PTB causes predominantly orthopaedic and integument injuries, whereas MVC results in thoracic and abdominal trauma. Survival to discharge is greater following PTB than MVC.
Keywords: orthopaedic trauma; soft tissue injury; abdominal trauma; motor vehicle trauma; pickup truck bed